The Enhancement of COVID-19 Severity on Coagulation Markers: a Cross-sectional Study in West Sumatra, Indonesia - Ika Kurnia Febrianti; Andani Eka Putra; Raveinal Raveinal; Aisyah Elliyanti (Majalah Kedokteran Andalas, 2024)
Objective: This study aimed to determine the description of the coagulation marker and how it implicates COVID-19 patients based on clinical outcomes in the form of enhancement severity and death. Method: The subjects were collected from patients with positive COVID-19 RT-PCR with medical records including demographic data, and laboratory results such as hemoglobin, hematocrit, leukocytes, platelets, coagulation markers (D-dimer, PT, and APTT), and patients outcomes post-treatment. Statistical analysis is performed by using chi-square and Mann-Whitney tests were considered statistically difference level of significant between variables. Result: The COVID-19 patients is classified into mild group with 27 subjects  (44.2%) and moderate-severe group 34 subjects (55.8%). Leukocytes, D-dimer, and PT levels significantly differed between mild and moderate-severe groups. All coagulation markers had a symptomatic effect on Covid-19 patients, increased D-dimer and prolonged prothrombin time in adult COVID-19 patients tend to be followed by the enhancement of severe symptoms and death